We Will Succeed: How Varying Success Expectancies and Socially Shared Regulation Shape Students' Collaborative Learning - Järvenoja, Hanna; Törmänen, Tiina; Turunen, Marjo; Lehtoaho, Emma (Journal of computer assisted learning, 2025)
ABSTRACT Background Collaborative learning offers benefits, but its potential is often undermined by motivational challenges. This study uses the situated expectancy‐value theory to explore how students' expectancies for success relate to group‐level regulation of learning during collaborative interactions. The study considers success expectancies both as a motivational condition for and a product of group‐level regulation during collaborative learning. Success expectancies are examined both as a condition for and a product of regulated learning, influencing students' engagement in motivation regulation and being shaped by it in turn. Objectives This study aims to understand the interconnection between group‐level regulation and students' success expectancies during collaborative learning and how this sets the stage for learning outcomes. Methods Forty‐eight eighth graders engaged in a four‐phase collaborative science task in small groups. Video recordings captured the groups' regulation, and each member completed situational self‐reports during different task phases. Stimulated recall interviews conducted after the task explored students' subjective justifications for variations in their situational expectancies for success. Employing multi‐channel sequence mining and clustering with mixture hidden Markov models, the study identified two types of group‐level regulation sequences: engaged in group‐level regulation and occasional cognitive group‐level regulation. Results and Conclusions Findings revealed characteristics of group‐level regulation sequences and showed that frequent engagement in cognitive and motivation regulation is associated with more positive success expectancies during and after the task. Success expectancies emerged as both a motivational condition and product of SSRL, correlating with task performance. Qualitative interview findings provided further insights into students' expectancies, shedding light on the motivational dynamics of collaborative learning.